If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4x + -1) * 2x = 0 Reorder the terms: (-1 + 4x) * 2x = 0 Reorder the terms for easier multiplication: 2x(-1 + 4x) = 0 (-1 * 2x + 4x * 2x) = 0 (-2x + 8x2) = 0 Solving -2x + 8x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '2x'. 2x(-1 + 4x) = 0 Ignore the factor 2.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-1 + 4x)' equal to zero and attempt to solve: Simplifying -1 + 4x = 0 Solving -1 + 4x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 4x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + 4x = 0 + 1 4x = 0 + 1 Combine like terms: 0 + 1 = 1 4x = 1 Divide each side by '4'. x = 0.25 Simplifying x = 0.25Solution
x = {0, 0.25}
| (3/x^2)+2/x | | 8-4y=8 | | 2(4x-5)-3= | | Y=1/2x-1 | | 8x+4x^2=9 | | 2-4y=8 | | -5x+3=y | | y(70-1y)-y=11 | | y(70-1y)+y=11 | | 4(s+2)+s-1= | | 2(2.9+4(2.9))=x | | 15-x=-22 | | 15-7=-22 | | 7.6+2.4(10)-10=x | | -3x+2x^2=-18 | | x+y=70 | | -11-8= | | -26/2+4 | | 2x^2y(3x+4y)= | | 7y=6X-14 | | 46.9/5=x | | 8.9+7.6(5)=x | | 8.9+7.6(5)5=x | | -26/2=4 | | 7y-8+6y-3= | | X/31=-9 | | 6x^2+9x=-3 | | 3(9-2y)+5y=20 | | y=2x^5-12x^3+10x | | 4+2d-4d= | | 6(10-3)=x | | 5=x/3+10 |